Geoarqueologia na planície costeira do Rio Grande do Sul: contribuições sobre a ocupação humana pré-histórica no litoral norte do RS - Raupp, Ismael da Silva (Universidade do Vale do Rio dos Sinos, 2015)
This work is an interdisciplinary research between Geology and Archeology. It aims to understand from a geoarchaelogycal perspective the relationship between the evolution of the northern portion of the coastal plain of the Rio Grande do Sul State (PCRS) and the preterit human occupation in the area. Our study area is located within the limits of the Arroio do Sal municipality. Ground Penetrating Radar (GPR) devices were used to acquire profiles in which were identified past coastal plain features favorable to human occupation of the region. From the data collected an interpretation of the possible scenario in which ancient human groups lived was elaborated, including the presence of currently filled back barrier lakes and lagoons. The same geophysical tool was used for subsurface acquisition in the shell mound named Marambaia I (RS-LN-312). The results have allowed the elaboration of a map of places prone to the presence of archaeological materials, hence hoping to reduce errors and costs in future excavation and therefore to preserve as much as possible the site integrity.
Keywords: Geoarqueologia; GPR; Planície costeira; Sambaqui; Geoarchaeology; Coastal plain; Shell mound; ACCNPQ::Ciências Exatas e da Terra::Geologia